Synthesis and Characterization of 4,4'-Diaminodiphenylmethane Schiff Bases - BIRICIK, NERMIN; KAYAN, CEZMI (Asian Journal of Chemistry, 2010)
Five novel Schiff bases were prepared from the reaction of 4,4'-diaminodiphenylmethane with acetylacetone, 3-chloroacetylacetone, salicylaldehyde, benzaldehyde and m-tolualdehyde. The synthesized Schiff bases were characterized by spectroscopic methods and elemental analysis.